Diversity and Evolution of Myxobacterial Type IV Pilus Systems - Sharma, Gaurav; Burrows, Lori L.; Singer, Mitchell (Frontiers in Microbiology, 2018)
Type IV pili (T4P) are surface-exposed protein fibers that play key roles in the bacterial life cycle via surface attachment/adhesion, biofilm formation, motility, and development. The order Myxococcales (myxobacteria) are members of the class Deltaproteobacteria and known for their large genome size and complex social behaviors, including gliding motility, fruiting body formation, biofilm production, and prey hunting. Myxococcus xanthus, the best-characterized member of the order, relies on the appropriate expression of 17 type IVa (T4aP) genes organized in a single cluster plus additional genes (distributed throughout the genome) for social motility and development. Here, we compared T4aP genes organization within the myxobacteria to understand their evolutionary origins and diversity. We found that T4aP genes are organized as large clusters in suborder Cystobacterineae, whereas in other two suborders Sorangiineae and Nannocystineae, these genes are dispersed throughout the genome. Based on the genomic organization, the phylogeny of conserved proteins, and synteny studies among 28 myxobacterial and 66 Proteobacterial genomes, we propose an evolutionary model for the origin of myxobacterial T4aP genes independently from other orders in class Deltaproteobacteria. Considering a major role for T4P, this study further proposes the origins and evolution of social motility in myxobacteria and provides a foundation for understanding how complex-behavioral traits, such as gliding motility, multicellular development, etc. might have evolved in this diverse group of complex organisms.